Maurice Halbwachs’s Life and Work - Urteaga, Eguzki (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Important figure of the French sociology of the first half in the 20th century, Maurice Halbwachshas realized a work of a great richness, which goes from the study of the social morphology to that of thecollective psychology, and which analyse matters such as consumption, social classes, memory of social groups, suicide, urban life, religion or demography. It consists also in numerous methodological writings dedicated to the quantification in social sciences and reveals to the French public a few foreign essential authors, like Werner Sombart, Thorstein Veblen, Max Weber, Robert Park, Ernest Burgess or John M.Keynes. This article tries to present the Maurice Halbwachs’s work and life which is often unknown.